2012
DOI: 10.1590/s0100-29452012000400038
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização fenológica, frutificação efetiva e produção de maçãs 'Eva' em clima semiárido no nordeste brasileiro

Abstract: RESUMO -O presente experimento foi conduzido de agosto de 2008 a dezembro de 2009,com o objetivo de caracterizar os estádios fenológicos, frutificação e produção de frutos de macieiras 'Eva', cultivadas em clima semiárido no Nordeste do Brasil. Dados fenológicos foram determinados em observações diárias, do estádio de gema dormente ao amadurecimento de frutas. Foram avaliadas as seguintes variáveis: i) a frutificação efetiva; ii) o número de frutos por planta; iii) a produção de frutos por planta (kg); e iv) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
1
12
1
1
Order By: Relevance
“…Despite the 'Eva' have presented significantly superiority for SS, the SS/TA ratio was higher in fruits of 'Princesa' (Table 4) that occurred due to the strongly lower TA of 'Princesa' fruits. This way, Cavalcante et al (2012) argued that higher TA and SS individually present a false parameter for fruit quality, while the SS/TA ratio has been considered a practical and reliable variable, especially for fruits consumed as fresh fruit. When compared to the data quoted in the scientific literature the average SS/TA ratio values of the present study are higher than those recorded by Chagas et cv.…”
Section: Results and Dicussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the 'Eva' have presented significantly superiority for SS, the SS/TA ratio was higher in fruits of 'Princesa' (Table 4) that occurred due to the strongly lower TA of 'Princesa' fruits. This way, Cavalcante et al (2012) argued that higher TA and SS individually present a false parameter for fruit quality, while the SS/TA ratio has been considered a practical and reliable variable, especially for fruits consumed as fresh fruit. When compared to the data quoted in the scientific literature the average SS/TA ratio values of the present study are higher than those recorded by Chagas et cv.…”
Section: Results and Dicussionmentioning
confidence: 99%
“…After hand defoliation (July 2012), the apple trees were pruned and treated with 0.8% hydrogen cyanamide and 3.0% mineral oil (Assist ® ), 3.0% of color fix (Hi-Light ® ) and 2.0% of adhesive (Iharaguen-S ® ) following the recommendation of Lopes et al (2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the feasibility of producing apple cultivars that require short time of cold weather in the semiarid conditions of the São Francisco River Valley (LOPES et al, 2012;LOPES et al, 2013;OLIVEIRA et al, 2013). Technically more extensive works, aiming to improve the cultivation of this species, may contribute to the crop diversification in irrigated areas of the Northeast of Brazil, and to the availability of fruits at times different from the traditional production regions (OLIVEIRA et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Os dados climáticos e de fases fenológicas foram submetidos a análises de correlação simples realizadas com o Programa assistat ® . a pereira 'triunfo' apresentou ciclo fenológico (Figura 1) de 144 dias (tabela 1), mostrando-se mais tardia que as cultivares 'housui' e 'Kousui', que completaram seu ciclo em 128 e 115 dias, respectivamente, quando submetidas às condições de cultivo do semiárido brasileiro (loPeS et al, 2013b). Foram necessários 23 dias para que as gemas passassem do estádio de dormência (a) para o de plena floração (F) (Tabela 1).…”
unclassified